For an analysis of landscape physiology applied to Pontal do Paranapanema - dos Passos, Messias Modesto [UNESP]; Gonçalves, Diogo Laércio [UNESP]; Maistro, Juliane [UNESP] (Universidad de Jaen, 2023)
The objective of this work is to analyze the physiology of the landscape in the Pontal do Paranapanema region, specifically in the Santo Antonio river basin, following three basic objectives: to lead to an understanding of the organization, functioning and dynamics of landscapes, to emphasize the study and the integrated analysis of the constituent elements of landscapes; understand and discuss concepts, laws and influences of anthropic actions. We opted for a dynamic typology that classifies geosystems according to their evolution. It takes into account three elements: system of evolution, stage reached in relation to the climax, general sense of dynamics, inspired by Erhart's theory of bioresistance. Two types of geosystems grouped into two different dynamic sets were distinguished. The analyzes of satellite images, photographs and observations on the ground help to explain the evolutionary processes.
Por una análisis de la fisiología del paisaje aplicado al Pontal do Paranapanema
Por uma análise da fisiologia da paisagem aplicada ao Pontal do Paranapanema
Keywords: Landscape physiology; Pontal do Paranapanema; Santo Antônio river basin